2000
DOI: 10.1074/jbc.m001280200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Selenoprotein Synthesis by Selenocysteine tRNA[Ser]Sec Lacking Isopentenyladenosine

Abstract: A common posttranscriptional modification of tRNA is the isopentenylation of adenosine at position 37, creating isopentenyladenosine (i(6)A). The role of this modified nucleoside in protein synthesis of higher eukaryotes is not well understood. Selenocysteyl (Sec) tRNA (tRNA([Ser]Sec)) decodes specific UGA codons and contains i(6)A. To address the role of the modified nucleoside in this tRNA, we constructed a site-specific mutation, which eliminates the site of isopentenylation, in the Xenopus tRNA([Ser]Sec) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
131
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(133 citation statements)
references
References 45 publications
1
131
1
Order By: Relevance
“…We tested whether the previously defined catalytic activity of Mod5 is required for tgm silencing by depleting its DMAPP substrate in two different ways (23)(24)(25). The first method was to treat cells with the drug Atorvastatin, which inhibits an early enzyme in DMAPP biosynthesis, 3-hydroxy-3-methyl-glutarylCoA (HMG-CoA) reductase (24).…”
Section: Significancementioning
confidence: 99%
“…We tested whether the previously defined catalytic activity of Mod5 is required for tgm silencing by depleting its DMAPP substrate in two different ways (23)(24)(25). The first method was to treat cells with the drug Atorvastatin, which inhibits an early enzyme in DMAPP biosynthesis, 3-hydroxy-3-methyl-glutarylCoA (HMG-CoA) reductase (24).…”
Section: Significancementioning
confidence: 99%
“…Furthermore, human prostate cancer PC3 cells treated with atorvastatin undergo autophagy, whereas simvastatin leads to the induction of apoptosis in HCT116 colorectal cancer cells and renal cell carcinoma cells (41). Statins also downregulate the mevalonate pathway and block the biosynthesis of cellular isoprenoids, including IPP, which are responsible for the post-translational modification of Sec-tRNA [Ser]Sec and the synthesis of GPX4 (6,35,42). Although there is no experimental evidence demonstrating the link between statins and ferroptosis, statins downregulate the mevalonate pathway, which is a crucial signaling event for GPX4 maturation.…”
Section: Metabolism and Ferroptosismentioning
confidence: 99%
“…To investigate the role of mcm 5 Um in UGA translation, a dominant-negative acting mutant tRNA [Ser]Sec that does not form the modified nucleotide i 6 A at position 37 (due to the in vitro mutagenesis of that position for an A to a G) and does not undergo ribose methylation at mcm 5 U34 was used (Warner et al 2000;Moustafa et al 2001 A − cells was assessed using each of the reporter constructs and shown to be greatly diminished compared to control cells (Fig. 6).…”
Section: Levels and Methylation Of Trnamentioning
confidence: 99%